HUBUNGAN MINAT PRESTASI PRAKTIK KERJA LAPANGAN DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII JASA BOGA SMK - Christina Bety Sukesi (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
The purpose of this study was to find out: (1) achievement of field work practice, (2) interest in entrepreneurship, and relationship between the achievements of fieldwork practice. This type of research is "ex-post facto". Data collection techniques used questionnaires and documentation. The data analysis technique used descriptive analysis and hypothesis testing used Product Moment which is preceded by normality test and linearity test. The results showed that Â (1) Field Work Achievement Results students are classified as high with an average value of 81.6 in the interval 70-85 with a frequency of 72.31%. (2) Interest in entrepreneurship of students in sufficient categories with a relative frequency of 49.23%.(3) there was a positive and significant relationship between the performance of fieldwork practices with an interest in entrepreneurship with a value of r count = 0.516> r table = 0.244.